2008
DOI: 10.1590/s1806-37132008001100004
|View full text |Cite
|
Sign up to set email alerts
|

Função pulmonar e força muscular respiratória em pacientes com doença renal crônica submetidos à hemodiálise

Abstract: Objective: To evaluate pulmonary function and respiratory muscle strength in chronic renal failure patients, correlating these variables with hemodialysis-related weight fluctuation; to study the correlation between the duration of hemodialysis and potential respiratory alterations. Methods: Seventeen patients (median age, 47 years; interquartile range, 41-52 years), submitted to three weekly hemodialysis sessions for a median of 27 months (interquartile range, 14-55) were evaluated. Twelve of the patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 16 publications
(25 reference statements)
2
24
0
15
Order By: Relevance
“…A study reported that abnormal findings, such as congestion in the pulmonary tree of such patients are frequently a result of bodily fluid overload in the interdialytic period, and greater weight gain during this period is associated with worsening of lung function (11) . Thus, the interdialytic weight gain appears to be an important variable to be considered in these patients, since their daily abrupt variation is related to the accumulation of liquids and hardly related to increased body mass (28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that abnormal findings, such as congestion in the pulmonary tree of such patients are frequently a result of bodily fluid overload in the interdialytic period, and greater weight gain during this period is associated with worsening of lung function (11) . Thus, the interdialytic weight gain appears to be an important variable to be considered in these patients, since their daily abrupt variation is related to the accumulation of liquids and hardly related to increased body mass (28) .…”
Section: Discussionmentioning
confidence: 99%
“…The latter is the main risk factor for developing coronary artery disease, cerebrovascular disease and pulmonary congestion (2,(4)(5)11) .…”
Section: Introductionmentioning
confidence: 99%
“…All tests were performed by a trained evaluator. For DG, the evaluations were conducted on the second and third day of dialysis in the week (Wednesday and Friday or Thursday and Saturday) 21 .…”
Section: Methodsmentioning
confidence: 99%
“…3,6,12,14 The most commonly found pulmonary alterations are as follows: limitation to air flow; obstructive disorders; a reduction in pulmonary diffusion capacity; and a decrease in respiratory muscle endurance and strength. 3,6,14 However, measuring respiratory muscle strength and function allows the early diagnosis of those changes, helping in establishing supervised training protocols.…”
Section: Repercussion Of An Intradialytic Physical Therapy Protocolmentioning
confidence: 99%
“…A new and challenging area for physical therapy is the physical and functional rehabilitation of patients with chronic kidney disease (CKD).¹ Chronic kidney disease can be defined, according to the Brazilian Society of Nephrology,² as the slow, progressive, and irreversible loss of renal function, a condition in which the kidneys have no functionality as a consequence of damage to the nephrons, [1][2][3] resulting in incapacity of the organism to maintain renal metabolic and hydroelectrolytic balance. [4][5] Renal dysfunction is characterized by a glomerular filtration rate (GFR) lower than 60 mL/ min/1.73m 2 , for more than three months, and, when GFR reaches levels lower than 15 mL/min/1.73m 2 , the renal dysfunction is called end-stage CKD.…”
Section: Introductionmentioning
confidence: 99%